Tissue-specific epigenetics of atherosclerosis-related ANGPT and ANGPTL genes. (28th January 2019) - Ehrlich, Kenneth C; Lacey, Michelle; Ehrlich, Melanie
Aim: To understand tissue-specific regulation of angiopoietin/angiopoietin-like ( ANGPT/ANGPTL ) genes (especially the five genes embedded in introns of host genes) and their association with atherosclerosis.Methods: Transcription and epigenomic databases from various normal tissues were examined in the vicinity of ANGPT1, ANGPT2, ANGPTL1, ANGPTL2, ANGPTL3, ANGPTL4  and ANGPTL8 .Results: We identified tissue-specific enhancer chromatin regions that are likely to regulate transcription of ANGPT/ANGPTL genes and were intragenic, intergenic or host gene-linked. In addition, we found atherosclerosis-linked differentially methylated regions associated with ANGPT2 and with sequences encoding miR-145, a microRNA that targets ANGPT2 mRNA in cancers.Conclusion: Our findings implicate enhancers as major contributors to tissue-specific expression of ANGPT/ANGPTL genes, which play critical roles in angiogenesis, atherosclerosis, cancer, and inflammatory and metabolic diseases.